Determining the fate of missing persons: The importance of archives for “dealing with the past” mechanisms - Baumgartner, Elisabeth; Ott, Lisa (International Review of the Red Cross, 2017)

On or off the record? Detecting patterns of silence about death in Guatemala’s National Police Archive - Guberek, Tamy; Hedstrom, Margaret (Archival Science, 2017)
This paper investigates how the production of police records was linked to the policies of repression and violence during Guatemala’s civil war. We provide empirical evidence from the Historical Archive of the Guatemalan National Police that the police used language, terminology and codes to record deaths in ways that produced silences about the level of violence during the height of repressive military rule. Using a dataset derived from a statistically valid sample of police records together with qualitative archival analysis, we find evidence of profound changes in the terminology used to record and report on deaths—changes that follow a pattern consistent with the policies of information control and concealment of the three different military regimes that ruled Guatemala between 1978 and 1985. We argue that researchers will need to consider the silences created through the selective use of terminology in documents when using archives to produce historical knowledge. Detecting and intercepting silence will be especially important as state records are increasingly sought in service of ongoing pursuits for truth and justice about past atrocities.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Rethinking, Representing, and Remembering the Cold War: Some Cultural Perspectives - Jarausch, Konrad H.; Ostermann, Christian F.; Etges, Andreas (Rethinking, Representing, and Remembering the Cold War: Some Cultural Perspectives, 2017)
Rethinking, Representing, and Remembering the Cold War: Some Cultural Perspectives was published in The Cold War on page 1.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Identity Politics and the East China Sea: China as Japan's ‘Other’ - Yennie Lindgren, Wrenn; Lindgren, Petter Y. (Asian Politics & Policy, 2017)
This article contributes to the relational IR literature on identity politics and Sino-Japanese relations. Theoretically, we develop Rumelili's framework for studying modes of differentiation by incorporating the sectoral characteristics of key discourse signs. Empirically, we apply this framework to the construction of Self and Other in the official Japanese security discourse regarding the Senkaku Islands dispute from 2010–2014, a period of dispute climax that is meaningful for studying the (re)production of Japan's understanding of China. The inclusiveness of the discourse signs that Japan uses to construct China possibly opens up for a positive evolution of Sino-Japanese relations, as there is space for progress if China's behavior—and Japan's interpretation of it—proves to be more peaceful, transparent, and law-abiding. The findings also suggest, however, that the strong sense of superiority in Japan (and China) vis-à-vis a subordinate Other may not bode well for Sino-Japanese relations.
Keywords: East China Sea; Japan; References - Boel et al. (2021), Archives and Human Rights; constructivism; identity; security policy; 东海; 关键词: 日本; 安全政策; 建构主义; 认同

Towards a ‘common’ view of difficult past? The representation of atomic bombings of Hiroshima and Nagasaki in trilateral teaching materials - Szczepanska, Kamila (Journal of Peace Education, 2017)
The centrality of atomic bombings of Hiroshima and Nagasaki in Japanese collective memory has been often perceived by the country’s neighbours, i.e. the People’s Republic of China and South Korea, as a pillar of the country’s (alleged) ‘victim consciousness’ and amnesia in regard to the suffering inflicted on others. For this reason, the matter of how Hiroshima and Nagasaki’s fate is discussed on the pages of joint teaching materials is an interesting puzzle. The article uses two supplementary history teaching materials published within a framework of trilateral cooperation between non-governmental actors from the PRC, South Korea and Japan (History that Opens the Future [Mirai o hiraku rekishi] and The New Modern and Contemporary History of East Asia [Atarashi Higashi Ajia no kingendaishi]) as case studies to investigate how the fate and meaning of Hiroshima and Nagasaki are represented in the above-mentioned books. The article discusses traces of contestation and negotiation over the representation of the atomic bombings emerging from relevant descriptions, and the extent to which the narrative on Japanese wartime suffering is included in these materials. The findings concerning the atomic bombings are discussed in relation to broader topic of reconciliation and alleviating the burden of wartime past in East Asia for the purpose of building peaceful future.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Press Conference by the Chief Cabinet Secretary October 27, 2017 (AM) - Suga, Yoshihide (Prime Minister of Japan and His Cabinet, 2017)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Press Conference by the Chief Cabinet Secretary October 13, 2017 (AM) | Prime Minister of Japan and His Cabinet - Nogami, Kotaro (2017)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Contested Memories in Chinese and Japanese Foreign Policy - Dian, Matteo (Chandos Publishing, 2017)
Contested Memories in Chinese and Japanese Foreign Policy explores the issue of memory and lack of reconciliation in East Asia. As main East Asian nations have never achieved a common memory of their pasts, in particular, the events of the Second World War and Sino-Japanese War, this book locates the issue of memory within International Relations theory, exploring the theoretical and practical link between the construction of a country’s identity and the formation and contestation of its historical memory and foreign policy.Provides an innovative theoretical frameworkDraws connections between the role of memory and foreign policyUses the interpretative theory of international relationsGives comparative perspective using the cases of China and JapanPresents in-depth analysis of the construction and contestation of national memory in China and Japan
Keywords: References - Boel et al. (2021), Archives and Human Rights

Netherlands Found Partially Liable for Srebrenica Deaths - BIRN (Balkan Insight, 2017)
A Dutch appeals court found the Netherlands partially liable for the deaths of around 300 Bosniaks from Srebrenica who were killed after being expelled from a Dutch UN peacekeepers’ base in 1995.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Where is my name? Afghan women fight for their own identity - Joya, Bahaar (Reuters, 2017)
In Afghanistan's patriarchal society, a woman's name should not be revealed, even on her grave.
Keywords: AFGHANISTAN; Afghanistan; Asia; Belief; Civil Liberties; Civil Rights; Fundamental Rights; Human Rights; Internet; NAME; Pacific; References - Boel et al. (2021), Archives and Human Rights; Religion; Science; Social Media; Technology; US; WOMEN; Women's Issues; World Wide Web

Trust Fund Unveils Reparations Plan for Katanga Victims - Wakabi, Wairagala (International Justice Monitor, 2017)
The International Criminal Court's (ICC's) Trust Fund for Victims (TFV) has published a plan for implementing reparation awards to 297 victims of crimes committed by former Congolese militia leader German Katanga. According to an order by ICC judges, each victim will receive an individual symbolic c
Keywords: References - Boel et al. (2021), Archives and Human Rights

Annual Report of the Inter-American Commission on Human Rights 2016 - Informe Anual 2016 - Lanza, Edison (OAS, 2017)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Mapping Archives for Dealing with the Past Processes - Peterson, Trudy Huskamp; Baumgartner, Elisabeth (Swisspeace, 2017)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Was the destruction of Old Mostar Bridge a war crime? - Hazan, Pierre (JusticeInfo.net, 2017)
To what extent does the destruction of an architectural masterpiece constitute a war crime if that masterpiece is also used for military purposes? What, too, if the destruction of such a monument, like the Old Mostar Bridge, causes psychological and physical harm to a civilian population now under siege? How should military objectives, damage to […]
Keywords: References - Comma (2020 1-2), Archives and Human Rights

UN Security Council adopts historic resolution for the protection of heritage - Unesco (UNESCO, 2017)
New York, 24 March 2017 - UNESCO Director-General Irina Bokova addressed today’s public briefing of the United Nations Security Council on “Maintenance of international peace and security: destruction and trafficking of cultural heritage by terrorist groups and in situations of armed conflict,” where the UN Security Council unanimously adopted resolution 2347 for the protection of heritage.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Caught On Video, Muslim’s Gory Slaying Angers Indians - BenarNews (Eurasia Review, 2017)
By Akash Vashishtha Indian activists blamed the government’s rightwing Hindu ideology Friday for a Muslim man’s gruesome killing, which was videotaped and posted online, and which police believe wa…
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Indian child brides sold in 'package deals' to Gulf men - Srivastava, Roli (news.trust.org, 2017)
"I was 14 and our neighbour told us that a rich Arab boy was looking for a bride. We went to meet him. He was not a boy. He was 62"
Keywords: References - Comma (2020 1-2), Archives and Human Rights

The history of the persecution of Myanmar's Rohingya - Abdelkader, Engy (The Conversation, 2017)
The persecution of the Rohingya goes back to 1948, the year when Myanmar achieved independence from the British.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Thailand: Trafficking Convictions Important Step Forward - Human Rights Watch (Human Rights Watch, 2017)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Full text of European Court of Human Rights Decision on the case Kolk and Kislyiy v. Estonia: Non-Applicability of Statutory Limitations to Crimes against Humanity. - Council of Europe (Derechos.org, 2017)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

For captured ISIS fighters in Iraq, justice is swift and conviction certain - Gallagher, Ash (Yahoo!life, 2017)
Yahoo News gets a rare look inside the courtroom where captured ISIS fighters are being tried in Iraq. The trials last about 20 minutes, convictions are virtually certain, and a lenient sentence is 15 years.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Wife of Princeton researcher held in Iran urges his release - Schreck, Adam; Tang, Didi (AP NEWS, 2017)
DUBAI, United Arab Emirates (AP) — The wife of a Princeton graduate student sentenced to 10 years behind bars in Iran called on authorities there to release him Tuesday, saying the Chinese-American man has been "unjustly imprisoned." Xiyue Wang was arrested nearly a year ago but his confinement only became known Sunday when Iran's judiciary announced his sentence, accusing him of "infiltrating" the country and sending confidential material abroad. The 36-year-old, described by Iranian authorities as holding Chinese and American citizenship, was in Iran doing research for his doctorate in late 19th and early 20th century Eurasian history when he was detained.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Online Harassment 2017 - Duggan, Maeve (Pew Research Center: Internet, Science & Tech, 2017)
Roughly four-in-ten Americans have personally experienced online harassment, and 62% consider it a major problem.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Jammu Chamber to launch ‘Identify & Kill’ campaign against Rohingya refugees - KL News Network (Kashmir Life, 2017)
Syed Junaid Hashmi Jammu Intensifying the campaign against the Rohingya Refugees and Bangladeshis living in Jammu, Jammu Chamber of Commerce and Industry (JCCI) Friday threatened to launch “Identify and Kill” campaign against them to force them to leave Jammu and other areas of the state where t...
Keywords: References - Comma (2020 1-2), Archives and Human Rights

The Yogyakarta Principles plus 10: Additional principles and state obligations on the application of international human rights law in relation to sexual orientation, gender identity, gender expression and sex characteristics to complement the Yogyakarta principles. - Grinspan, Mauro Cabral; Carpenter, Morgan; Ehrt, Julia; Kara, Sheherezade; Narrain, Arvind; Patel, Pooja; Sidoti, Chris; Tabengwa, Monica (yogyakartaprinciples.org, 2017)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Slavery in India’s Brick Kilns & the Payment System - Anti-slavery (Anti-slavery, 2017)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Identifying Nazi victims from brain slides - Osterath, Osterath (dw.com, 2017)
The Nazis murdered about 300,000 people with mental illnesses. Some of the victims' brains were handed over for research, and some are still held at German institutes. It's time to identify the victims.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Court rules airline can ban Israeli passengers - Pearson, Alexander (dw.com, 2017)
Kuwait Airways canceled an Israeli passenger's ticket because of their citizenship. Nothing wrong with that, said a court in Frankfurt — and provoked an outcry.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Mothers’ names put on wedding certificates - Hellen, Caroline Wheeler and Nicholas (The Times, 2017)
Mothers’ names will finally be included on marriage certificates under plans expected to be approved by the Home Office in the new year. At present, the official documents record only the names and occupations of the fathers of the bride and groom.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Despite Ban, Invasive Virginity Tests Remain Prevalent in Afghanistan - Nader, Zahra; Mashal, Mujib (The New York Times, 2017)
Months after the president vowed to keep justice officials from ordering the examinations, found to be invalid, the tests are still traumatizing women.
Keywords: Afghanistan; Afghanistan Independent Human Rights Commission; Forensic Science; Ghani, Ashraf; Human Rights and Human Rights Violations; References - Comma (2020 1-2), Archives and Human Rights; Sex Crimes; Special Inspector General for Afghanistan Reconstruction; Women and Girls; Women for Afghan Women; Women's Rights

Safe Havens for Archives at Risk - Gurciullo, Sebastian (Literary and Artistic Archives: the blog of the Section on Literary and Artistic Archives of the International Council on Archives, 2017)
As described in earlier posts, SLA has continued to support work being conducted on Archival Safe Havens (cases of archives in extreme danger which may, as a last resort, be physically moved to a safe location or be digitally copied and the copies transferred to a trusted repository.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

News from the ICA Human Rights Working Group - 2017-12 (December) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-11 (November) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-10 (October) - Peterson, Trudy Huskamp (ICA, 2017)
Keywords: Oct'17 newsletter link to Nov'17.

News from the ICA Human Rights Working Group - 2017-09 (September) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-08 (August) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-07 (July) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-06 (June) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-05 (May) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-04 (April) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-03 (March) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-02 (February) - Peterson, Trudy Huskamp (ICA, 2017)

News from the ICA Human Rights Working Group - 2017-01 (January) - Peterson, Trudy Huskamp (ICA, 2017)